Thermal diffusivity and perfusion constants from in vivo MR-guided focussed ultrasound treatments: a feasibility study. (19th May 2018) - Dillon, Christopher R.; Rieke, Viola; Ghanouni, Pejman; Payne, Allison
Abstract: Purpose: This study investigates the feasibility of non-invasively determining thermal diffusivity ( α ) and the Pennes perfusion parameter ( w ) from pre-clinical and clinical magnetic resonance-guided focussed ultrasound (MRgFUS) temperature data. Materials and methods: Pre-clinical MRgFUS experiments were performed in rabbit muscle ( N  = 3, 28 sonications) using three-dimensional MR thermometry. Eight sonications were made in a clinical QA phantom with two-dimensional thermometry. Retrospective property determination was performed on clinical uterine fibroid ( N  = 8, 9 sonications) and desmoid tumour ( N  = 4, 7 sonications) data. The property determination method fits an analytical solution to MRgFUS temperatures in the coronal MR plane, including all temperatures acquired during heating and one cooling image. When possible, additional cooling data were acquired for property determination. Results: Rabbit α and w from Heating Data ( α  = 0.164 mm 2 s −1, w =  7.9 kg m −3  s −1 ) and Heating and Cooling Data ( α  = 0.146 mm 2 s −1, w =  3.3 kg m −3  s −1 ) were within the range of gold-standard invasive measurements, with >50% reduction in variability by including cooling data. QA phantom property determination with cooling data yielded properties within 3% of expected values ( α  = 0.144 mm 2 s −1, w =  0.0 kg m −3  s −1 ), a difference that was not statistically significant ( p =  0.053). Uterine fibroid (Heating Data: α  = 0.212 mm 2 s −1, w  = 11.0 kg m −3  s −1 ) and desmoid tumour (Heating & Cooling Data: α  = 0.245 mm 2 s −1, w =  4.7 kg m −3  s −1 ) properties are feasible but lack independent verification. Conclusions: Thermal diffusivity and the Pennes perfusion parameter can be obtained from in vivo data and with clinical MRgFUS protocols. Property values are consistently improved by including cooling data. The utility of this property determination method will increase as clinical protocols implement improved temperature imaging.